1989
DOI: 10.1016/0014-5793(89)81093-2
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of a new cysteine proteinase inhibitor from pig leucocytes

Abstract: The primary structure of a pig leucocyte cysteine proteinase inhibitor, also called cathelin, was determined. The sequence was obtained from analyses of peptides isolated from the chymotryptic, endoproteinase Lys-C and protease V8 digests, and by analysis of the peptides derived from the hydrolysis of the aspartyl-prolyl bond of the carboxymethylated inhibitor. The inhibitor consists of 96 residues. The N-terminal residue of the inhibitor is pyrrolidonecarboxylic acid. The amino acid sequence. of cathelin sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
107
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 17 publications
1
107
0
1
Order By: Relevance
“…It has been suggested that all these proteins are members of a novel family of leukocyte proteins with antibacterial, LPS-binding and proteinase-inhibitory activities [8]. The N-terminal region is similar to the protein sequence of pig cathelin which had previously been isolated from pig blood leukocytes [9]. Therefore, it has been speculated that cathelin is the N-terminal fragment of a pig homolog of antibacterial peptides [8].…”
Section: Introductionmentioning
confidence: 96%
“…It has been suggested that all these proteins are members of a novel family of leukocyte proteins with antibacterial, LPS-binding and proteinase-inhibitory activities [8]. The N-terminal region is similar to the protein sequence of pig cathelin which had previously been isolated from pig blood leukocytes [9]. Therefore, it has been speculated that cathelin is the N-terminal fragment of a pig homolog of antibacterial peptides [8].…”
Section: Introductionmentioning
confidence: 96%
“…The prosequence which is present in the precursors of these peptides is highly identical to the sequence of a protein termed cathelin. This protein was isolated from porcine leukocytes [40], and is likely to be the proregion of a processed precursor of this type, from which the C-terminal antimicrobial peptide has been released ( of precursors, and this term will be used herewith to indicate molecules with a cathelin-like proregion and a C-terminal antimicrobial domain. Several mismatches in the 5' regions indicate that, in general, cathelicidins do not originate by posttranscriptional processing.…”
Section: Introductionmentioning
confidence: 99%
“…Although these peptides show marked diversity in structure and antimicrobial spectrum, the precursors of many antibiotic peptides of porcine [2 6], bovine [7][8][9][10] and rabbit [11,12] origin contain a highly conserved preproregion that is homologous to cathelin, a putative cysteine-proteinase inhibitor originally isolated from pig leukocytes [13,14]. Several of these cathelin-associated peptides have been isolated and characterized, including porcine PR-39 [15] and protegrins PG-1, 2 and 3 [16]; bovine Bac 5 [17,18], indolicidin 9 [19] and cyclic dodecapeptide [20]; and rabbit p15 [12] and CAP 18 [11].…”
Section: Introductionmentioning
confidence: 99%